Investigation of Changes in Biochemical Parameters in Some Diseases Occurring During the Transition Period in Simmental Cows - Safak, T.; Yilmaz, O.; Risvanli, A. (Israel Veterinary Medical Assoc, 2023)
The transition period is important in cows. This study was conducted to evaluate the effects of retained fetal membranes (RFM), clinical mastitis, and metritis on biochemical and selected mineral levels in Simmental cows. Cows were divided into five groups; cows with RFM (n=17), clinical mastitis (n=25), metritis (n=21) and postpartum healthy cows (n=21) within 21 days postpartum, and also prepartum healthy cows (n=20) in the 15 +/- 5 days before the expected parturition date. The activity of alkaline phosphatase (ALP) (85.18 +/- 15.83 U/L), aspartate transaminase (AST) (123.02 +/- 19.15 U/L), and gamma-glutamyl transferase (GGT) (28.18 +/- 2.66 U/L) in the metritis group increased compared to the prepartum healthy cows. Moreover, GGT (41.83 +/- 14.61 U/L) and a myocardial band of creatine kinase (CK-MB) (155.25 +/- 27.85 U/L) activities were highest in the RFM group, while creatine kinase - N-acetyl-cysteine activity (CKNAC) (540.45 +/- 157.67 U/L) and creatinine concentration (2.29 +/- 0.88 mg/dL) were observed in the metritis group. Total protein (6.39 +/- 0.38 g/dL) concentration was highest in the case of mastitis. Urea, on the other hand, was highest in the metritis group with a concentration of 61.40 +/- 17.38 mg/dL. Our results showed changes in the biochemical profile of cows with RFM, clinical mastitis, and metritis. Biomarker profiles were determined using receiver-operator characteristic (ROC) curves. It was determined that activities of = 89 (U/L) AST, = 24 (U/L) GGT, and = 106 (U/L) CK-MB for metritis, = 21(U/L) GGT for RFM, and = 105 (U/L) CK-MB for mastitis can be used in the preliminary diagnosis. Also, further studies with a larger cow cohorts are recommended.
Keywords: Cows; Mastitis; Metritis; Receiver Operating Characteristics; Transition Period